Shifts in discharge‐concentration relationships as a small catchment recover from severe drought. Issue 4 (1st March 2014) - Burt, Tim P.; Worrall, Fred; Howden, Nicholas J. K.; Anderson, Malcolm G.
Abstract This paper provides evidence of the recovery of a small, moorland catchment to a severe drought, the most extreme on record in the UK. We present a detailed water quality time series for the post‐drought recovery period, from the first significant storm event at the end of the drought through three very wet months during which time the catchment fully wetted up. High‐frequency observations were obtained using pump water samplers, at 15‐min intervals for storm events and 2 hourly at other times. There are significant shifts in discharge‐concentration response as the catchment wets up; initial behaviour is very different to later storms. Extreme drought may become more common in a warmer world, so it is increasingly important to understand water quality response during and after such episodes, if their impact on water resources and in‐stream ecology is to be better anticipated. Copyright © 2014 John Wiley & Sons, Ltd.